2020
DOI: 10.21037/tcr-2019-eaoc-05
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia in aging, obesity, and cancer

Abstract: Sarcopenia, defined as loss of muscle mass, strength and physical performance, is a hallmark of aging and is invariably associated with perturbation of amino acid metabolism, increased muscle protein catabolism relative to anabolism, and loss of muscle fibers. Sarcopenia may be associated with general loss of body mass, or it may also occur along with obesity [sarcopenic obesity (SO)]. Although sarcopenia is associated with multiple comorbidities in older adults, its effects may even be more severe in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 135 publications
(144 reference statements)
1
28
0
1
Order By: Relevance
“…Sarcopenia can be defined as a pathological loss of skeletal muscle mass characterized by essential structural changes in muscle quality, which occurs in older adults and shows functional impairment and/or strength reduction [ 55 ]. Aging is related to a decline in muscle mass and strength [ 56 ] but only when this decline becomes pathological (sarcopenia) does this process lead to adverse health outcomes [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia can be defined as a pathological loss of skeletal muscle mass characterized by essential structural changes in muscle quality, which occurs in older adults and shows functional impairment and/or strength reduction [ 55 ]. Aging is related to a decline in muscle mass and strength [ 56 ] but only when this decline becomes pathological (sarcopenia) does this process lead to adverse health outcomes [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenic obesity is more common in older adults (≥50 years old) [ 109 ], and the prevalence in individuals with cancer can vary substantially between 1% and 41.7%, as shown in Table 3 . This range of prevalence in several studies can be related to the different criteria used for the diagnosis of sarcopenic obesity, to the various types of cancer and their staging, aspects that limit understanding the panorama of occurrence and reveals the need for more research with other types of cancer not yet investigated.…”
Section: Epidemiological and Clinical Evidence Of The Association Between Sarcopenic Obesity And Cancermentioning
confidence: 99%
“…It has been stated that sarcopenic obesity adversely impacts treatment tolerance, long-term expectations and is an important indicator of adverse outcomes and a prognostic factor for complications in cancer patients [ 109 ]. In the present study, we concluded that there is still a very limited number of studies evaluating the impacts of sarcopenic obesity on several clinical and treatment variables of different types of cancer.…”
Section: Epidemiological and Clinical Evidence Of The Association Between Sarcopenic Obesity And Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…An adequate protein intake can reduce the incidence and severity of sarcopenia in cancer patients [ 56 ]. It has been demonstrated that a dietary program with energy and protein rich meals and snacks can improve muscle strength and performance status of lung cancer patients [ 57 , 58 ].…”
Section: Food and Dietary Plans In The Prevention/control Of Lung mentioning
confidence: 99%